Assess the status of professional endurance of female Rowing regatta in national youth team at Danang National Sports Center - Hung, N. X. (International Journal of Physical Education, Fitness and Sports, 2020)
In Rowing, racing, the athlete must control the boat legally and compete to overcome all obstacles in weight, water andwind resistance... to achieve the highest performance. This shows that the athlete must have a good physical level, especially a level of professional endurance, to overcome drag in the long run. As such, endurance is a very important physical quality and directly affects the performance of Rowing athletes.